2016
DOI: 10.1016/bs.irn.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

BK Channels in the Central Nervous System

Abstract: Large conductance Ca2+- and voltage-activated K+ (BK) channels are widely distributed in the postnatal central nervous system (CNS). BK channels play a pleiotropic role in regulating the activity of brain and spinal cord neural circuits by providing a negative feedback mechanism for local increases in intracellular Ca2+ concentrations. In neurons, they regulate the timing and duration of K+ influx such that they can either increase or decrease firing depending on the cellular context, and they can suppress neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
170
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(176 citation statements)
references
References 340 publications
3
170
0
Order By: Relevance
“…Several mechanisms control the size and duration of the Ca 2+ -signals at the active zone, thereby generating temporally restricted micro-and nano-domains of Ca 2+ that determine the extent of release (e.g., see Fedchyshyn & Wang, 2005;Bucurenciu et al, 2008;Vyleta & Jonas, 2014). Among the most important of these mechanisms is the control of the AP duration by BK-channels (Fakler & Adelman, 2008;Contet et al, 2016;Griguoli et al, 2016). BK-channels are Ca 2+ -activated large-conductance K +channels that limit the duration of an AP, thereby controlling the extent of Ca 2+ -channel opening and of neurotransmitter release per AP.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms control the size and duration of the Ca 2+ -signals at the active zone, thereby generating temporally restricted micro-and nano-domains of Ca 2+ that determine the extent of release (e.g., see Fedchyshyn & Wang, 2005;Bucurenciu et al, 2008;Vyleta & Jonas, 2014). Among the most important of these mechanisms is the control of the AP duration by BK-channels (Fakler & Adelman, 2008;Contet et al, 2016;Griguoli et al, 2016). BK-channels are Ca 2+ -activated large-conductance K +channels that limit the duration of an AP, thereby controlling the extent of Ca 2+ -channel opening and of neurotransmitter release per AP.…”
Section: Introductionmentioning
confidence: 99%
“…AMG44 also normalized BK channel physiology in dissociated DRGs from EAE mice as well as mRNA levels of the β 4 and β 1 auxiliary subunits of BK channels ( Fig. 9, 10 (53). To this effect, a reduction in BK channel current in the DRG is also associated with nerve injury (54,55) and inflammation-induced pain (56)(57)(58).…”
Section: Discussionmentioning
confidence: 92%
“…BK Ca channels play an important role in regulation of neuronal function . In neurons, the BK Ca channel colocalizes with voltage‐gated calcium channel and controls the cellular activity via negative feedback regulation of Ca 2+ influx . Activation of BK Ca channel leads to cellular membrane hyperpolarization and subsequent inhibition on voltage‐gated calcium channel opening and excessive Ca 2+ influx .…”
Section: Discussionmentioning
confidence: 93%
“…[15] In neurons, the BK Ca channel colocalizes with voltage-gated calcium channel [25] and controls the cellular activity via negative feedback regulation of Ca 2+ influx. [26] Activation of BK Ca channel leads to cellular membrane hyperpolarization and subsequent inhibition on voltage-gated calcium channel opening and excessive Ca 2+ influx. [27] It was found that administration of BMS-204352, a BK Ca channel opener significantly decreased cortical infarct volume in rats subjected to middle cerebral artery occlusion.…”
Section: Discussionmentioning
confidence: 99%